Systematic literature review on wireless power transmission - et. al., Dharani. M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In modern days, many power transfer technologies have been developed with and without cables. But plug-in cables have numerous drawbacks, such as exposed wires, bulky cables, and bad environmental impacts. Therefore, research on wireless power transmission (WPT) paid attention to researchers, academicians, and businesses in the automation industries. The wireless power transmission system (WPTS) is more popular to apply in various systems whichinclude televisions, household robots, laptops, and cellular phones due to its convenience and safety. In this article, the historical background of WPT technology, “radiative and non-radiative” wireless power transfer techniques are studied and also, evaluations of various “radiative and non-radiative” WPT techniques are tabulated.At last, the difficulties and future scopes of WPT innovation are introduced.